2022
DOI: 10.3389/fncel.2022.837166
|View full text |Cite
|
Sign up to set email alerts
|

Potential Roles of Enterochromaffin Cells in Early Life Stress-Induced Irritable Bowel Syndrome

Abstract: Irritable bowel syndrome (IBS) is one of the most common functional gastrointestinal disorders, also known as disorders of the gut–brain interaction; however, the pathophysiology of IBS remains unclear. Early life stress (ELS) is one of the most common risk factors for IBS development. However, the molecular mechanisms by which ELS induces IBS remain unclear. Enterochromaffin cells (ECs), as a prime source of peripheral serotonin (5-HT), play a pivotal role in intestinal motility, secretion, proinflammatory an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 239 publications
(392 reference statements)
1
9
0
Order By: Relevance
“…Short-chain fatty acids (SCFAs) are mainly composed of acetic acid, propionic acid, and butyric acid, which play a crucial role in the gut (54). A recent systematic review and metaanalysis revealed that compared with healthy controls the levels of propionic acid and butyric acid were decreased in IBS-C patients, while the level of butyric acid was increased in IBS-D patients (55). The metabolism of bile acids (BAs) may be to do with IBS, and it has been demonstrated that the level of BAs was related to visceral pain and colon transit.…”
Section: Discussionmentioning
confidence: 99%
“…Short-chain fatty acids (SCFAs) are mainly composed of acetic acid, propionic acid, and butyric acid, which play a crucial role in the gut (54). A recent systematic review and metaanalysis revealed that compared with healthy controls the levels of propionic acid and butyric acid were decreased in IBS-C patients, while the level of butyric acid was increased in IBS-D patients (55). The metabolism of bile acids (BAs) may be to do with IBS, and it has been demonstrated that the level of BAs was related to visceral pain and colon transit.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Bile secretion can regulate visceral pain perception and improve visceral hypersensitivity in IBS patients ( Ní Dhonnabháín et al, 2021 ). The increased expression of bile acid in fecal, primary bile acid in liver and bile acid receptor Takeda G protein-coupled receptor 5 (TGR5) in colon in most patients with IBS-D is closely related to the severity of diarrhea symptoms ( Walters, 2021 ; Wei et al, 2021 ), and the TGR5-ECS-5-HT signaling pathway may play an important role in the pathophysiology of IBS ( Tao et al, 2022 ). Bile acids can control the circadian variation of the metabolite uric acid through the regulation of xanthine oxidase by PPARα ( Kanemitsu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…When EC cells ar exposed to intraluminal pressure or chemical and mechanical stimulation, serotonin i released either apically to the gut lumen or basolaterally to the lamina propria. Upon it release, serotonin may take several possible routes, including having a direct influence on the gut microbiota, exerting influence on intracellular signaling by acting on 5-HT recep tors (5-HTRs), or being reuptook by surrounding epithelial and immune cells via the ser otonin reuptake transporter (SERT, encoded by the SLC6A4 gene), or entering the blood In blood, serotonin is present as free serotonin or it is taken up by platelets via SERT (ap proximately 95%) [57,58]. Any excess serotonin in the cells is degraded by monoamin oxidase (MAO), resulting in the production of 5-hydroxyindoleacetic acid (5-HIAA) which is mainly excreted in urine.…”
Section: Increased Interstitial Serotonin Availability In Ibd Patientsmentioning
confidence: 99%